Adsorptive removal of Pb2+ from wastewater using ZnO-Biochar nanocomposite - Hifsa Mudassar; Kiran Hina; Usman Ghani; Qadeer Afzaal; Anis Ali Shah; Shifa Shaffique; Hosam O. Elansary (Scientific Reports)
Abstract The discharge of lead (Pb2+) from industries, which is harmful to water, human health and food chain, poses a serious risk. Due to the remarkable ability of ZnO biochar nanocomposite to remove Pb²⁺ from wastewater, it gained significant attention in environmental research. This study was conducted to determine how effectively the prepared ZnO-Biochar nanocomposite removed Pb²⁺ from wastewater. Fourier transmission infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to examine the functional groups and surface morphology of the ZnO-Biochar nanocomposite, respectively. The structure of ZnO-Biochar nanocomposite with rough and porous surface performed the positive association in surface adsorption of Pb²⁺ pollutant. A batch-experimentation conducted under a variety of conditions, including initial Pb²⁺ concentration (50–200 mg L⁻¹), adsorbent dosage (0.05–0.25 g), pH (2–12), and contact time (0–240 min) to evaluate the removal rates as well as adsorption capacities, within an emphasis on environmental impact. This study proves that ZnO-Biochar nanocomposite has a 90.30% removal rate for Pb²⁺. The ZnO-Biochar nanocomposite proved an impressive maximum adsorption capacity (qmax) of 79.302 mg/g, as determined through the implementation of the Langmuir model. A linear pseudo-first order and pseudo-second order model having R2 values of 0.867 and 0.899 respectively, show the best fit for the experimental data concerning Pb²⁺. Experiments conducted in this work demonstrate the exciting potential of the prepared material for promoting sustainable treatment of industrial wastewater.